Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22168492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interactions of Selected Olivacine Derivatives with DNA and Topoisomerase II

Abstract: Olivacine and ellipticine are model anticancer drugs acting as topoisomerase II inhibitors. Here, we present investigations performed on four olivacine derivatives in light of their antitumor activity. The aim of this study was to identify the best antitumor compound among the four tested olivacine derivatives. The study was performed using CCRF/CEM and MCF-7 cell lines. Comet assay, polarography, inhibition of topoisomerase II activity, histone acetylation, and molecular docking studies were performed. Each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…Etoposide, a standard Topoisomerase inhibitor, was On the other hand, the binding interaction of the anticancer agent with DG13 was reported as pivotal interaction as this interaction stimulates the formation of DNA damage that is toxic to cancer cells 41 . Similar binding modes with DA12 and DC8 through π-π stacking were also reported for the most active benzoxazole and olivacine derivatives as the anticancer agents 40,42 .…”
Section: Molecular Docking Study On the Inhibition Of Topoisomerase I...supporting
confidence: 76%
“…Etoposide, a standard Topoisomerase inhibitor, was On the other hand, the binding interaction of the anticancer agent with DG13 was reported as pivotal interaction as this interaction stimulates the formation of DNA damage that is toxic to cancer cells 41 . Similar binding modes with DA12 and DC8 through π-π stacking were also reported for the most active benzoxazole and olivacine derivatives as the anticancer agents 40,42 .…”
Section: Molecular Docking Study On the Inhibition Of Topoisomerase I...supporting
confidence: 76%
“…From the three-dimensional structure, it was known that 1,3,6,8-tetrahydroxyxanthone was located near the DNA α-helix and amino acid residues of chain A. Two-dimensional structure revealed that 1,3,6,8tetrahydroxyxanthone interacted with Adenine12, Guanine13 and Cytosine14 nitrogen base residues, as well as Arginine503, Lysine505, and Alanine521 amino acid residues, through hydrogen bonds on the active site of TopIIα. It was reported that the interactions with Adenine12 and Guanine13 were pivotal to stimulating the damage of cancer cells' DNA thus raising the apoptosis response [36] [37]. Moreover, the 1,3,6,8-tetrahydroxyxanthone interacted with Glutamic acid522 through pi-anion interaction, with Arginine503 and Alanine521 through pi-alkyl interaction, as well as Glycine504, Isoleusine506, and Asparagine520 through van der Waals interactions.…”
Section: Molecular Docking Of Hydroxyxanthonementioning
confidence: 99%
“…Interaction of 1,3,6,8tetrahydroxyxanthone with Adenine12 and Guanine13 nitrogen bases on the active site of TopIIα led to suppression of the DNA replication and transcription of cancer cells [36] [37]. Meanwhile, the interactions of 1,3,6,8tetrahydroxyxanthone with Glutamine767 and Methionine769 through hydrogen bonds, as well as Aspartic acid831 through van der Waals interaction, on the active site of EGFR caused the less signal for the cancer cells to proliferate, differentiate and survive [7] [8].…”
Section: Molecular Docking Of Hydroxyxanthonementioning
confidence: 99%